A brief introduction to the fabrication and synthesis of graphene based composites for the realization of electromagnetic absorbing materials. Issue 3 (10th January 2017) - Lv, Hualiang; Guo, Yuhang; Yang, Zhihong; Cheng, Yan; Wang, Luyuan Pual; Zhang, Baoshan; Zhao, Yue; Xu, Zhichuan J.; Ji, Guangbin
Abstract : This review gives a brief introduction to graphene-based composites. Their synthesis methods and electromagnetic energy attenuation mechanisms are summarized in detail. Abstract : Owing to the fast development of wireless information technologies at the high-frequency range, the electromagnetic interference problem has been of increasing significance and attracting global attention. One key solution for this problem is to develop materials that are able to attenuate the unwanted electromagnetic waves. The desired properties of these materials include low reflection loss value, wide attenuation band, light weight, and low cost. This review gives a brief introduction to graphene-based composites and their electromagnetic absorption properties. The ultimate goal of these graphene absorbers is to achieve a broader effective absorption frequency bandwidth ( f E ) at a thin coating thickness ( d ). Representative and popular composite designs, synthesis methods, and electromagnetic energy attenuation mechanisms are summarized in detail. The two key factors, impedance matching behavior and attenuation ability, that determine the electromagnetic behavior of graphene-based materials are given particular attention in this article.